Evaluation of water absorption and solubility of digitally and conventionally produced temporary fixed materials - Sahin Zeynep; Ozer Nazire Esra (Balkan Stomatological Society, 2024)
Background/Aim: The study aims to evaluate water sorption and solubility of conventional and digitally produced temporary fixed materials. Material and Methods: A total of 40 disc-shaped specimens were prepared from two conventionally produced temporary fixed materials: bis-acrylic composite resin (Protemp 4-PT) and acrylic resin (Dentalon plus-DP) and two digitally produced [3D printing (MACK4D Temp-MT) and CAD/CAM milling (On Dent-OD)]. The prepared disks were dried in a desiccator until they reached a constant mass. They were then kept in distilled water at 37°C for 1 week and weighed. The weights of the specimens, which were again subjected to conditions similar the initial drying procedure, were measured. Water absorption and solubility values were calculated by formula. The data obtained were analyzed using 1-way analysis of variance (ANOVA) and the Tamhane or Tukey post hoc test (a=.05). Results: Water absorption values of the PT group (24.16±8.1 µg/mm 3) were statistically higher than all other groups (p= 0.001). However, there was no significant difference in the pairwise comparisons of OD, MT, and DP groups (p>0.05). When the water solubility values were analyzed, DP group (0.49±2.01 µg/mm 3) showed no significant difference with the PT group (1.69±2.2 µg/mm 3) (p=0.402), while they were higher than OD (-3.96±0.84 µg/mm 3) and MT (-10.29±1.37 µg/ mm 3) groups. In addition, a significant difference was observed in the water solubility values of CAD/CAM-3D groups (p<0.05). Conclusions: All of test groups were found to be within the values recommended by ISO standards. It can be inferred that the PT material may cause the most staining.